Interaction-induced Electric Properties of van der Waals Complexes - Cherepanov, Victor N.; Kalugina, Yulia N.; Buldakov, Mikhail A. (Springer International Publishing : Imprint: Springer, 2017)
This brief explains the theory of the interaction-induced electrical properties of van der Waals complexes. It focuses on the interaction-induced electrical dipole moments, polarizabilities and first hyperpolarizabilities of atom-atomic, atom-molecular and molecular-molecular van der Waals complexes.
Keywords: Chemistry.; Chemistry, Physical and theoretical.; Atoms.; Physics.; Matter.; Optical materials.; Electronic materials.; elektronické knihy; electronic books